High-performance sodium hybrid capacitor enabled by presodiated Li4Ti5O12 - Kim, Myeong-Seong; Roh, Ha-Kyung; Jeong, Jun Hui; Lee, Geon-Woo; Nazarian-Samani, Masoud; Chung, Kyung Yoon; Kim, Kwang-Bum (ELSEVIER SCIENCE BV, 2019)
For the first time, we propose herein high-energy sodium hybrid capacitors comprising Na+ intercalated Li4Ti5O12 anode and activated carbon cathode. The design of sodium hybrid capacitors takes full advantage of Li4Ti5O12's lower working potential plateau for Na+ intercalation than for Li+ intercalation. The lower potential plateau facilitates not only wider cell voltage of sodium hybrid capacitors (3.4 V) compared to that of lithium hybrid capacitors (3.0 V), but also enhanced capacity utilization of activated carbon, thereby giving sodium hybrid capacitors higher energy over lithium hybrid capacitors assembled with the same electrode configuration. High-tap density Li4Ti5O12/reduced graphene oxide microsphere composites are synthesized via one-step spray drying and a subsequent heat-treatment to realize high-performance sodium hybrid capacitors. The sodium hybrid capacitors deliver a high energy density of 83 Wh kg(-1), which is twice as high as the energy density of lithium hybrid capacitors (42 Wh kg(-1)). In addition, the sodium hybrid capacitors exhibit excellent cycling stability (93% capacity retention after 30,000 cycles). To the best of our knowledge, this is the first report to demonstrate that simple switching of Li4Ti5O12 from the Li+ to Na+ system can double the energy density of the hybrid capacitor.
Keywords: CARBON NANOTUBES; RATE CAPABILITY; ANODE MATERIAL; GRAPHENE; OXIDE; NANOSHEETS; NITROGEN; NANOPARTICLES; FABRICATION; SHEETS